Representações iconográficas de São Paulo sob a ótica de Aurélio Becherini - Pires, Jhonatan Ferreira (2022)
The present study aims to approach the photographic work of Aurélio Becherini in the city of São Paulo between the years 1900 to 1930. His photographs were widely circulated in the printed media of that period, mainly the newspaper O Estado de S. Paulo and the comparative albums of the city. of São Paulo, commissioned by Mayor Washington Luis. The photographs and Becherini made use of iconographic references that preceded and preceded the emergence of photography, such as the first landscape paintings of the city in the early 19th century. Throughout the 19th century photography was very taxable of painting. In order to understand the iconographic roots of representation of the city of São Paulo, and how it influenced Becherini's photographs, the present research seeks to apply the iconographic method developed by the Walburg School, disseminated by one of its main representatives, Erwin Panofsky